A multiscale modified asphalt additive, method of making and method of use

CN121537740BActive Publication Date: 2026-10-30ZHONGLU JIAOKE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511711263.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2026-10-30
Estimated Expiration
2045-11-20

AI Technical Summary

Technical Problem

[0005]本发明的第一个目的在于提供一种多尺度改性沥青添加剂,利用主添加剂和辅添加剂共同通过物理化学作用完成对沥青混合料的协同改性;解决现有聚烯烃改性剂分布不均匀、相容性差的问题,使得沥青混合料兼具高温抗变形、低温抗裂、中温抗疲劳性能

Benefits of technology

(1)本发明通过改变传统聚烯烃类改性剂的直投工艺,将多尺度改性沥青添加剂分为拌缸直投的主添加剂和预先改性沥青的辅添加剂,通过微米尺度主添加剂和纳米尺度辅添加剂中不同维度纳米改性剂间范德华力作用下的自组装及极性基团键合作用的定向吸附排列,在沥青基体中将辅添加剂中碳纳米管和石墨烯组装排列在主添加剂的聚烯烃表面,利用沥青对氧化石墨烯层间的溶胀效应及碳纳米管的桥接铆钉和纳米TiO2的锚固作用,构建了相互连接的多尺度改性的微-纳结构体系,进一步增加了改性剂与沥青之间接触面积,提高了界面区域分子间的相互作用能力,实现了沥青混合料在不损伤高温抗变形能力的同时,大幅提升低温抗裂、中温抗疲劳性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121537740B_ABST
    Figure CN121537740B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of road asphalt additive, and particularly relates to a multi-scale modified asphalt additive, a preparation method and a use method. The multi-scale modified asphalt additive is composed of a main additive and an auxiliary additive, and the main additive includes, in terms of weight percentage, 60-80 parts of modified polyolefin, 20-30 parts of zero-dimensional functionalized nano TiO2 and 4-8 parts of an interface agent; and the auxiliary additive includes 0.4-0.8 parts of one-dimensional aminated carbon nanotubes and 0.2-0.6 parts of two-dimensional graphene oxide. The main additive provided by the present application has good dispersion uniformity and compatibility in asphalt through functional group modification and crystalline structure transformation; the auxiliary additive is uniformly dispersed in asphalt in advance to form nano modified asphalt, and the main additive is directly added to enhance the nano modified asphalt during mixing, and the micro-nano structure system constructed by the main additive and the auxiliary additive in asphalt realizes the synergistic modification of asphalt at different scales, so that the mechanical properties of modified asphalt mixture at different temperatures are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road asphalt additives, and specifically to a multi-scale modified asphalt additive, its preparation method, and its application method. Background Technology

[0002] In recent years, with the significant increase in road traffic volume, heavy traffic volume has also risen sharply. Under the traffic load environment of high traffic volume and heavy axle load, asphalt pavement is prone to structural damage such as rutting, cracking, and subsidence in the early stages of use, greatly reducing the service life of the pavement structure. Therefore, in order to achieve long service life and sustainable development of asphalt pavement, higher requirements have been placed on the performance of asphalt pavement, which in turn has led to continuous improvement in the quality requirements of asphalt pavement materials, especially asphalt and asphalt modifiers.

[0003] Currently, in terms of asphalt, a large amount of engineering practice can prove that existing modified asphalt can effectively improve the shortcomings of base asphalt and greatly improve its road performance; in terms of asphalt modifiers, polyolefin modifiers such as anti-rutting agents are the most widely used, which can significantly improve the deformation resistance of asphalt pavement at high temperatures. However, polyolefin modifiers still have the following problems: (1) Polyolefin is a semi-crystalline polymer material, which generally has a high degree of crystallinity. The modification effect on asphalt mainly depends on the degree of crystallinity and the distribution of crystal regions. During the cooling process, polyolefin melt will generate an uneven large-sized spherulite crystal structure, so that polyolefin mainly exists in the asphalt in an uneven large particle form. As a result, although polyolefin modified asphalt has good high-temperature anti-rutting ability, its fatigue resistance and crack resistance at medium and low temperatures are greatly weakened. (2) The special molecular structure of polyolefins makes them non-polar, so they have poor compatibility with weakly polar asphalt. The thickness of the two-phase interface layer is very small, and there is a very obvious and definite phase interface, which makes polyolefin modified asphalt prone to segregation. Furthermore, polyolefins are easy to migrate in asphalt mixtures, which has a negative impact on their performance.

[0004] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the present invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention

[0005] The first objective of this invention is to provide a multi-scale modified asphalt additive that utilizes the main additive and auxiliary additives to synergistically modify asphalt mixtures through physicochemical action; it solves the problems of uneven distribution and poor compatibility of existing polyolefin modifiers, enabling asphalt mixtures to possess high-temperature deformation resistance, low-temperature crack resistance, and medium-temperature fatigue resistance.

[0006] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A multi-scale modified asphalt additive, composed of main additives and auxiliary additives, calculated by weight parts, The main additive comprises the following components: 60-80 parts of modified polyolefin, 20-30 parts of zero-dimensional functionalized nano-TiO2, and 4-8 parts of interface agent; The auxiliary additives include the following components: 0.4-0.8 parts of one-dimensional aminated carbon nanotubes and 0.2-0.6 parts of two-dimensional graphene oxide.

[0007] The multi-scale modified asphalt additive provided by this invention involves directly adding the main additive in a certain proportion during the mixing of asphalt mixtures, while the auxiliary additive is added to the base asphalt in advance and stirred to form nano-modified asphalt. The main additive and auxiliary additives work together to synergistically modify the asphalt mixture at different scales by assembling interconnected micro-nano structures through the van der Waals forces between nano-modifiers of different dimensions and the bonding between different polar groups.

[0008] Preferably, the modified polyolefin is obtained by melt extrusion grafting modification of polyolefin with the main graft monomer maleic anhydride, the co-graft monomer styrene, and an initiator. The mass ratio of polyolefin, maleic anhydride, styrene, and initiator is 100:2~3:0.4~0.6:0.1~0.3. Under the action of the initiator, the main graft monomer maleic anhydride and the co-graft monomer styrene are chemically bonded to the polyolefin molecular chain through a melt free radical grafting reaction. The addition of styrene can increase the grafting rate of maleic anhydride and inhibit its homopolymerization. After graft modification, the highly polar anhydride groups are randomly arranged on the polyolefin molecular chain, which reduces the crystallinity of the polyolefin by disrupting its regular arrangement structure, and improves its compatibility with asphalt through the bonding of the anhydride groups with asphalt, thus improving the uniformity of polyolefin dispersion in asphalt.

[0009] Furthermore, the polyolefin has a molecular weight of 15,000 to 25,000 and a melt index of 40 to 50 g / 10 min at 190°C and a load of 2.16 kg. A molecular weight greater than 15,000 reduces the repulsion between the polyolefin and asphalt, ensuring the polyolefin's enhancing effect on asphalt performance; a molecular weight less than 25,000 results in a lower melt viscosity at the mixing and compaction temperature, perfectly matching the construction temperature of the base asphalt; and a high melt index ensures that the polyolefin retains good rapid melting properties even after the introduction of nano-modifier fillers.

[0010] Furthermore, the initiator is a mixture of benzoyl peroxide (BPO) and tert-butyl peroxide (TBPB) in a 1:1 mass ratio. The initiator decomposes at a certain temperature to generate free radicals, initiating the grafting reaction. BPO has a relatively low decomposition temperature, providing a high concentration of initial free radicals in the early stages of the reaction, ensuring a rapid start to the grafting reaction and improving reaction efficiency. TBPB has a higher decomposition temperature and decomposes more slowly in the early stages of the extruder, but it can continuously provide free radicals in the middle and later stages of the reaction, maintaining a sufficient concentration of free radicals in the reaction system and preventing the reaction from stopping due to premature consumption of BPO. This ensures that maleic anhydride and styrene monomers have sufficient opportunities to contact and graft with the free radicals of the polyolefin macromolecules. The combination of the two ensures that the free radical generation rate throughout the reaction process is optimally matched with the monomer diffusion rate and the melt state of the polyolefin.

[0011] As a further preferred embodiment, the method for preparing the modified polyolefin includes the following steps: A1. At room temperature, dissolve maleic anhydride, styrene, and initiator in acetone; the mass ratio of acetone to maleic anhydride is 30:2~3; specifically, add 2~3 parts maleic anhydride, 0.4~0.6 parts styrene, and 0.1~0.3 parts initiator to 30 parts acetone, and use medium-speed mechanical stirring to dissolve them completely, avoiding the introduction of too much air due to vigorous stirring; A2. Add the polyolefin to the solvent in A1 and stir until homogeneous. Specifically, while continuously stirring, gradually add 100 parts of the polyolefin to the solvent in A1, using a warm water bath or jacket heating method, controlling the temperature at 40-60℃, until all the acetone evaporates, ensuring thorough mixing of the polyolefin with the grafted monomer and initiator. The reaction should be carried out in a fume hood or open container to facilitate the diffusion and removal of acetone vapor. Slow purging with nitrogen or dry air can also be used to accelerate evaporation and remove oxygen from the system. A3. The polyolefin in A2 is melt-extruded and granulated at 120~160℃ using a twin-screw extruder with a screw speed of 200~400rpm. Under the combined action of heat and shear force, the components achieve uniform mixing and interfacial reaction at the molecular level to form modified polyolefin.

[0012] Preferably, the zero-dimensional functionalized nano-TiO2 is prepared by solution grafting of nano-TiO2 and silane coupling agent. By grafting silane coupling agent onto nano-TiO2, the siloxane alkyl end of the silane coupling agent undergoes a hydrolytic condensation reaction with the hydroxyl groups on the surface of nano-TiO2 to form a strong Si-O-Ti covalent bond. The long-chain organic part of the silane coupling agent covers the surface of TiO2, changing it from hydrophilic to lipophilic, which greatly reduces the surface free energy of nano-TiO2, weakens the van der Waals forces between them, reduces the agglomeration of nano-TiO2 in polyolefins and asphalt, and improves its compatibility and dispersion uniformity in modified polyolefins and asphalt.

[0013] The nano-TiO2 has a rutile crystalline morphology, a particle size of 20-25 nm, and a specific surface area of ​​50-60 m². 2 / g. The silane coupling agent is KH560, and the amount of the silane coupling agent is 10%~20% of the mass fraction of nano-TiO2. The particle size range setting can ensure that nano-TiO2 has good dispersibility in polyolefins and refine the polyolefin grains; rutile nano-TiO2 has a relatively lower surface free energy, and further by setting the specific surface area range, it has a lower surface free energy and is more easily dispersed uniformly in polyolefins.

[0014] As a further preferred method, the preparation process of zero-dimensional functionalized nano-TiO2 is as follows: B1. Prepare a 50 g / L suspension of 50 g nano TiO2 with deionized water, adjust the pH to 4.0 with ω=5% acetic acid solution, then disperse at high speed with emulsifier for 20 min, and then disperse by ultrasonication for 30 min before transferring to a three-necked flask.

[0015] B2. Add 10%~20% by mass of silane coupling agent KH560 of nano-TiO2 to the three-necked flask in B1, place it in a constant temperature water bath to maintain the reaction temperature at 80℃, and react for 4~8 hours under stirring. Then, after centrifugation, filtration and washing, and extraction with anhydrous ethanol for 2 hours, the zero-dimensional functionalized nano-TiO2 is obtained after vacuum drying and pulverization at 60℃.

[0016] Preferably, the interface agent is one or more of naphthenic oil and white oil, and the kinematic viscosity of the interface agent at 40°C is 10~20 mm. 2 The use of an interface agent can avoid uneven mixing caused by the size difference between the modified polyolefin and the functionalized nano-modifier particles; low-viscosity naphthenic oil or white oil can form a uniform oil film on the surface of the modified polyolefin particles, and the kinematic viscosity range setting can ensure the thickness of the oil film of the interface agent on the surface of the modified polyolefin, thereby ensuring the uniformity of mixing.

[0017] Preferably, the specific surface area of ​​the one-dimensional aminated carbon nanotubes is 250~300 m². 2 The carbon nanotubes have an average diameter of 10-15 nm, an average length of 3-5 μm, and an amino content of 0.45 wt%. The amino groups, acting as active reaction sites, can chemically react with the anhydrides of modified polyolefins, the epoxy groups of functionalized TiO2, and the carboxyl groups of graphene oxide, forming chemical bridges. The specific surface area range ensures suitable van der Waals forces between the carbon nanotubes; excessive van der Waals forces can lead to aggregation, while insufficient forces can cause structural defects. The aspect ratio range ensures that the carbon nanotubes can effectively transfer stress under load without entanglement, bending, or structural collapse. The amino content ensures a certain degree of polarity, enhancing dispersion affinity and compatibility in the asphalt matrix.

[0018] Preferably, the two-dimensional graphene oxide is obtained by sequentially oxidizing natural graphite powder with concentrated sulfuric acid and potassium permanganate. Under the action of strong acid and oxidizing agent, oxygen-containing functional groups are inserted into the interlayer of natural graphite, and the layers are exfoliated and oxidized to form graphene oxide. The mass ratio of natural graphite powder, concentrated sulfuric acid, and potassium permanganate is 10:40~50:4~8. Preferably, the particle size of the natural graphite powder is 3~20 μm. This particle size range ensures that the graphite powder is completely oxidized during the oxidation process, eliminating the need for centrifugation.

[0019] Furthermore, the C / O atomic ratio and interlayer spacing of the two-dimensional graphene oxide were characterized by X-ray photoelectron spectroscopy and X-ray diffraction. The C / O atomic ratio of the two-dimensional graphene oxide was 1.3~1.5, ensuring sufficient polar groups to achieve good compatibility and chemical bonding, while retaining sufficient intrinsic structure to maintain its excellent reinforcing ability. The interlayer spacing was 0.8~0.9 nm, which makes it easier to be peeled into fewer layers, or even a single layer, under the shear forces experienced during asphalt mixing and construction, achieving nanoscale dispersion in asphalt.

[0020] As a further preferred embodiment, the preparation method of the two-dimensional graphene oxide includes the following steps: C1. Add concentrated sulfuric acid to natural graphite powder and stir until homogeneous; specifically, under an ice-water bath, add 40-50 parts of concentrated sulfuric acid to a three-necked flask containing 10 parts of natural graphite powder and stir until homogeneous. C2. Add potassium permanganate and react at medium temperature; specifically, slowly add 4-8 parts of potassium permanganate to the three-necked flask of C1, stir evenly, and then raise the temperature to 35℃ and react for 30-50 minutes. C3. After adding deionized water, react at high temperature to obtain two-dimensional graphene oxide. Specifically, add 50 parts of deionized water to the C2 reaction system, raise the temperature to 90℃ and continue the reaction for 10~30 minutes. After the reaction is completed, add 5 parts of hydrogen peroxide, filter and wash, and then sonicate for 30 minutes to form two-dimensional graphene oxide.

[0021] The second objective of this invention is to provide a method for preparing multi-scale modified asphalt additives. Through a precisely controlled process, the internal structure of the main additive and auxiliary additives is optimized, laying the material foundation for the successful construction of multi-scale micro-nano composite structures in asphalt mixtures.

[0022] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A method for preparing a multi-scale modified asphalt additive includes the following steps: S1. Premix the modified polyolefin and the interface agent in a certain proportion; S2. Mix the zero-dimensional functionalized nano-TiO2 and the materials in S1 evenly; S3. The material from S2 is fed into a twin-screw extruder and melted, extruded, and granulated to form the main additive; S4. Mix one-dimensional aminated carbon nanotubes and two-dimensional graphene oxide evenly to form an auxiliary additive.

[0023] Specifically, the preparation method of the multi-scale modified asphalt additive includes the following steps: S1. Spray 4-8 parts of interface agent evenly onto 60-80 parts of modified polyolefin while stirring, so that the interface agent forms a uniform oil film on the surface of modified polyolefin. S2. Add 20-30 parts of zero-dimensional functionalized nano-TiO2 into the material in S1 and mix them evenly by high-speed stirring. S3. The material that is uniformly mixed in S2 is melted, extruded and granulated to form the main additive. The temperature of the melt extrusion section is 120~160℃. The high-intensity shear field provided by the twin-screw extruder effectively breaks up the agglomerates of nano-TiO2. Through the lubrication of the interfacial agent, the polymer melt is forced to penetrate and coat each nanoparticle, achieving nanoscale uniform dispersion of TiO2 in the polyolefin matrix. The high temperature of the extrusion process provides activation energy for the interfacial chemical reaction, causing the epoxy groups of KH560 on the surface of nano-TiO2 to undergo a ring-opening reaction with the anhydride groups of the modified polyolefin, forming a strong covalent bond interface rather than a fragile physical adsorption. The final granulated main additive particles have a pre-constructed micro-nano composite masterbatch with polyolefin as the continuous phase, uniformly dispersed and strongly bonded nano-TiO2. The structure is stable, easy to store and transport, and achieves rapid melting in subsequent mixing.

[0024] S4. Add 0.4~0.8 parts of one-dimensional aminated carbon nanotubes and 0.2~0.6 parts of two-dimensional graphene oxide into a high-speed disperser and mix evenly to form an auxiliary additive.

[0025] Mechanical force is used to interweave and entangle one-dimensional fibrous carbon nanotubes with two-dimensional sheet-like graphene oxide, forming a preliminary physical interwoven network. This greatly increases the probability of contact between the two in the subsequent asphalt premixing process, helping to form a stable synergistic reinforcing network more quickly and efficiently.

[0026] The third objective of this invention is to provide a method for using multi-scale modified asphalt additives, which solves the problem of dispersion and action of additives of different dimensions in complex asphalt-mineral aggregate systems through a staged feeding process, thereby achieving synergistic modification.

[0027] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A method for using a multi-scale modified asphalt additive includes the following steps: P1. Add the additives at 1% of the asphalt mass ratio into the asphalt storage tank and stir until homogeneous. Premixing provides carbon nanotubes and graphene oxide with a mild and sufficient time and energy to depolymerize, disperse, and pre-form a nano-network in the asphalt. P2. Add the main additive to the mixing tank at a ratio of 0.8% to 1.4% of the mineral mass and mix it with the mineral. Utilize the high-speed impact and friction of the hot mineral to make the main additive melt rapidly and coat the surface of the aggregate, so as to achieve uniform distribution and interface optimization at the macro scale. P3. Add asphalt binder at 3.9% to 4.5% of the aggregate mass ratio and mix thoroughly. P4. Add mineral powder according to the production mix ratio and mix evenly to form modified asphalt mixture; P5. Place the well-mixed modified asphalt mixture from P4 into a material truck for transportation, paving, and compaction.

[0028] Furthermore, a specific method for using a multi-scale modified asphalt additive is as follows: P1. Add the auxiliary additives at 1% of the asphalt mass ratio into the asphalt storage tank, and stir at 1000 rpm for 1 hour at 160~170℃ to form nano-modified asphalt. P2. Add the main additive to the mixing tank of the asphalt mixing plant at a ratio of 0.8% to 1.4% of the aggregate mass, and dry mix it with the hot aggregate preheated to 180 to 190°C for 15 to 20 seconds, so that the main additive is completely melted and spread on the surface of the hot aggregate.

[0029] P3. Inject nano-modified asphalt preheated to 160-170℃ into the mixing tank of the asphalt mixing plant at a ratio of 3.9% to 4.5% of the aggregate mass, and continue mixing for 30-40 seconds. P4. Add mineral powder into the mixing tank of the asphalt mixing plant according to the production mix ratio, and continue to stir for 30-40 seconds until there are no white specks, forming a modified asphalt mixture. P5. Place the modified asphalt mixture prepared in P4 into a material truck for transportation, paving, and compaction.

[0030] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention changes the traditional direct injection process of polyolefin modifiers, and divides the multi-scale modified asphalt additives into main additives directly injected into the mixing tank and auxiliary additives for pre-modified asphalt. Through the self-assembly of different dimensions of nano-modifiers in the micron-scale main additive and nano-scale auxiliary additives under the action of van der Waals forces and the directional adsorption arrangement of polar group bonding, carbon nanotubes and graphene in the auxiliary additives are assembled and arranged on the polyolefin surface of the main additive in the asphalt matrix. By utilizing the swelling effect of asphalt on the interlayer of graphene oxide and the bridging rivets of carbon nanotubes and the anchoring effect of nano TiO2, a multi-scale modified micro-nano structure system is constructed, which further increases the contact area between the modifier and the asphalt, improves the interaction ability between molecules in the interface region, and realizes that the asphalt mixture can significantly improve the low-temperature crack resistance and medium-temperature fatigue resistance without damaging the high-temperature deformation resistance.

[0031] (2) The multi-scale modified asphalt additive provided by the present invention introduces zero-dimensional functionalized nano-TiO2 into the modified polyolefin, thereby transforming the polyolefin from a large-sized spherulite structure to a small-sized spherulite grain. The grain refinement improves the uniformity of polyolefin distribution in asphalt, effectively avoids the influence of uneven crystallization on asphalt performance, and improves its compatibility with zero-dimensional functionalized nano-TiO2 and matrix asphalt through strong polar anhydride groups, thereby improving the problem of insufficient fatigue performance and crack resistance of traditional polyolefin modified asphalt at medium and low temperatures.

[0032] (3) The multi-scale modified asphalt additive provided by the present invention avoids the agglomeration of a large number of nano-modifiers in the direct mixing and blending and granulation process with polyolefins by pre-dispersing one-dimensional aminated carbon nanotubes and two-dimensional graphene oxide components in asphalt. It also inhibits the self-aggregation and agglomeration of additives in asphalt by relying on the bonding effect of polar groups and the steric hindrance characteristics brought about by dimensional differences, and further improves its dispersion uniformity in asphalt. The unique morphology of carbon nanotubes allows them to exist in the swollen graphene layers in a bridging form, forming a certain three-dimensional spatial structure, which significantly increases the contact area between nano-modifiers and asphalt, improves stress transfer ability, and thus significantly improves the mechanical properties of asphalt matrix at low temperature, medium temperature and high temperature. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 This is a schematic diagram illustrating the synergistic effect of multi-scale modified asphalt main additives and auxiliary additives in asphalt. Figure 2 This is a schematic diagram illustrating the interaction between multi-scale modified asphalt additives in asphalt.

[0035] Figure reference numerals: 1. Modified polyolefin; 2. Graphene oxide; 3. Aminated carbon nanotubes in different distribution states; 4. Functionalized nano-TiO2; 5. Active sites of graphene oxide; 6. Active sites of aminated carbon nanotubes; 7. Asphalt component; 8. Bonding effect between nano-modifiers and polar groups; 9. Active sites of modified polyolefin. Detailed Implementation

[0036] To further illustrate the technical means and effects adopted by the present invention to achieve its intended purpose, the specific implementation methods, features, and effects of a multi-scale modified asphalt additive, its preparation method, and its application method according to the present invention are described in detail below. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention.

[0037] Sources of raw materials used in the implementation methods and comparative examples: Polyolefins: MB9500, TJZS-2650, DMDA-8950 (melt index of 40~50g / 10min at 190℃ and 2.16kg load), commercially available.

[0038] Nanomodifiers and raw materials: nano TiO2, aminated carbon nanotubes, carbon nanotubes, graphene, natural graphite powder, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0039] Grafting monomers: maleic anhydride, styrene, silane coupling agent KH560, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0040] Initiators: Benzoyl peroxide, tert-butyl peroxide, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0041] Interface agents: white oil, naphthenic oil, commercially available.

[0042] Other reagents: concentrated sulfuric acid, acetone, potassium permanganate, hydrogen peroxide, acetic acid, anhydrous ethanol, Sinopharm Chemical Reagent Co., Ltd.

[0043] Asphalt: 70# base asphalt, Lanzhou Refinery.

[0044] Example 1: The multi-scale modified asphalt additive provided in this embodiment includes, by weight fraction, 76 parts of modified polyolefin, 20 parts of zero-dimensional functionalized nano-TiO2, and 4 parts of interface agent as the main additive; and by weight fraction, the auxiliary additive includes the following components: 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of two-dimensional graphene oxide. Preparation of modified polyolefins: A1. Add 2 parts maleic anhydride, 0.4 parts styrene, and 0.1 parts initiator to 30 parts acetone and dissolve them completely. A2. Add 100 parts of polyolefin (MB9500) to the solvent in A1 and stir continuously until all the acetone evaporates, so that the polyolefin is fully mixed with the grafted monomer and initiator. A3. The material in A2 is melt-extruded and granulated using a twin-screw extruder at 120~160℃ to form modified polyolefin.

[0045] Preparation of zero-dimensional functionalized nano-TiO2: B1. Prepare a 50 g / L suspension of 50 g nano TiO2 with deionized water, adjust the pH to 4.0 with ω=5% acetic acid solution, then disperse at high speed with emulsifier for 20 min, and then disperse by ultrasonication for 30 min before transferring to a three-necked flask.

[0046] B2. Add 10% by mass of nano-TiO2 and silane coupling agent KH560 to the three-necked flask in B1, place it in a constant temperature water bath to maintain the reaction temperature at 80℃, react for 4 hours under stirring, then centrifuge, filter and wash, extract with anhydrous ethanol for 2 hours, and dry and pulverize under vacuum at 60℃ to obtain functionalized nano-TiO2.

[0047] The preparation process of two-dimensional graphene oxide is as follows: C1. Under an ice-water bath, add 40 parts of concentrated sulfuric acid to a three-necked flask containing 10 parts of natural graphite powder and stir until homogeneous. C2. Slowly add 4 parts of potassium permanganate to the three-necked flask of C1, stir well, and then raise the temperature to 35℃ and react for 50 minutes. C3. After adding 50 parts of deionized water to the C2 reaction system, the temperature is raised to 90℃ and the reaction continues for 10 minutes. After the reaction is completed, 5 parts of hydrogen peroxide are added, filtered and washed, and then ultrasonically treated for 30 minutes to form two-dimensional graphene oxide.

[0048] Furthermore, the C / O atomic ratio of the two-dimensional graphene oxide is 1.39, and the interlayer spacing is 0.82 nm.

[0049] A method for preparing a multi-scale modified asphalt additive includes the following steps: S1. Spray 4 parts of interface agent evenly onto 76 parts of modified polyolefin while stirring, so that the interface agent forms a uniform oil film on the surface of modified polyolefin. S2. Add 20 parts of functionalized nano-TiO2 evenly into the material in S1 and mix them evenly by high-speed stirring. S3. The material that is uniformly mixed in S2 is melted, extruded and granulated to form the main additive. The temperature of the melt extrusion section is 120~160℃.

[0050] S4. Add 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of two-dimensional graphene oxide into a high-speed disperser and mix evenly to form an auxiliary additive.

[0051] The method of using a multi-scale modified asphalt additive is as follows: P1. Add the additives at 1% of the asphalt mass ratio into the asphalt storage tank, and stir at 1000 rpm for 1 hour at 160~170℃ to form nano-modified asphalt.

[0052] P2. Add the main additive to the mixing tank of the asphalt mixing plant at 0.8% of the mass ratio of the aggregate, and dry mix it with the hot aggregate preheated to 180-190℃ for 15-20 seconds; so that the main additive is completely melted and spread on the surface of the hot aggregate.

[0053] P3. Inject nano-modified asphalt preheated to 160-170℃ into the mixing tank of the asphalt mixing plant at 4.5% of the aggregate mass ratio, and continue mixing for 30-40 seconds. P4. Add mineral powder into the mixing tank of the asphalt mixing plant according to the production mix ratio, and continue to stir for 30-40 seconds until there are no white particles, forming a modified asphalt mixture. P5. Place the modified asphalt mixture prepared in P4 into a material truck for transportation, paving, and compaction.

[0054] Example 1 Performance Test: Table 1. Detection results of multi-scale modified asphalt additives in Example 1 Example 2: The multi-scale modified asphalt additive provided in this embodiment, calculated by weight fraction, includes 69 parts of modified polyolefin, 25 parts of zero-dimensional functionalized nano-TiO2, and 6 parts of interface agent.

[0055] Preparation of modified polyolefins: A1. Add 2.5 parts maleic anhydride, 0.5 parts styrene, and 0.2 parts initiator to 30 parts acetone and dissolve them completely. A2. Add 100 parts of polyolefin (TJZS-2650) to the solvent in A1 and stir continuously until all the acetone evaporates, so that the polyolefin is fully mixed with the grafted monomer and initiator. A3. The material in A2 is melt-extruded and granulated using a twin-screw extruder at 120~160℃ to form modified polyolefin.

[0056] Preparation of zero-dimensional functionalized nano-TiO2: B1. Prepare a 50 g / L suspension of 50 g nano TiO2 with deionized water, adjust the pH to 4.0 with ω=5% acetic acid solution, then disperse at high speed with emulsifier for 20 min, and then disperse by ultrasonication for 30 min before transferring to a three-necked flask.

[0057] B2. Add 15% by mass of nano-TiO2 and silane coupling agent KH560 to the three-necked flask in B1, place it in a constant temperature water bath to maintain the reaction temperature at 80℃, react for 6 hours under stirring, then centrifuge, filter and wash, extract with anhydrous ethanol for 2 hours, and dry and pulverize under vacuum at 60℃ to obtain functionalized nano-TiO2.

[0058] The preparation process of two-dimensional graphene oxide is as follows: C1. Under an ice-water bath, add 45 parts of concentrated sulfuric acid to a three-necked flask containing 10 parts of natural graphite powder and stir until homogeneous. C2. Slowly add 6 parts of potassium permanganate to the three-necked flask of C1, stir well, and then raise the temperature to 35℃ and react for 40 minutes. C3. After adding 50 parts of deionized water to the C2 reaction system, the temperature is raised to 90℃ and the reaction continues for 20 minutes. After the reaction is completed, 5 parts of hydrogen peroxide are added, filtered and washed, and then ultrasonically treated for 30 minutes to form two-dimensional graphene oxide.

[0059] Furthermore, the C / O atomic ratio of the two-dimensional graphene oxide is 1.42, and the interlayer spacing is 0.87 nm.

[0060] A method for preparing a multi-scale modified asphalt additive includes the following steps: S1. Spray 6 parts of interface agent evenly onto 69 parts of modified polyolefin while stirring, so that the interface agent forms a uniform oil film on the surface of modified polyolefin. S2. Add 25 parts of functionalized nano-TiO2 evenly into the material in S1 and mix them evenly by high-speed stirring. S3. The material that is uniformly mixed in S2 is melted, extruded and granulated to form the main additive. The temperature of the melt extrusion section is 120~160℃.

[0061] S4. Add 0.6 parts of one-dimensional aminated carbon nanotubes and 0.4 parts of two-dimensional graphene oxide into a high-speed disperser and mix evenly to form an auxiliary additive.

[0062] The method of using a multi-scale modified asphalt additive is as follows: P1. Add the additives at 1% of the asphalt mass ratio into the asphalt storage tank, and stir at 1000 rpm for 1 hour at 160~170℃ to form nano-modified asphalt.

[0063] P2. Add the main additive to the mixing tank of the asphalt mixing plant at 1.1% of the mass ratio of the aggregate, and dry mix it with the hot aggregate preheated to 180-190℃ for 15-20 seconds; so that the main additive is completely melted and spread on the surface of the hot aggregate.

[0064] P3. Inject nano-modified asphalt preheated to 160-170℃ into the mixing tank of the asphalt mixing plant at 4.2% of the aggregate mass ratio, and continue mixing for 30-40 seconds. P4. Add mineral powder into the mixing tank of the asphalt mixing plant according to the production mix ratio, and continue to stir for 30-40 seconds until there are no white particles, forming a modified asphalt mixture. P5. Place the modified asphalt mixture prepared in P4 into a material truck for transportation, paving, and compaction.

[0065] Example 2 Performance Test: Table 2. Detection results of multi-scale modified asphalt additives in Example 2 Example 3: The multi-scale modified asphalt additive provided in this embodiment, calculated by weight fraction, includes 62 parts of modified polyolefin, 30 parts of zero-dimensional functionalized nano-TiO2, and 8 parts of interface agent.

[0066] Preparation of modified polyolefins: A1. Add 3 parts maleic anhydride, 0.6 parts styrene, and 0.3 parts initiator to 30 parts acetone and dissolve them completely. A2. Add 100 parts of polyolefin (DMDA-8950) to the solvent in A1 and stir continuously until all the acetone evaporates, so that the polyolefin is fully mixed with the grafted monomer and initiator. A3. The material in A2 is melt-extruded and granulated using a twin-screw extruder at 120~160℃ to form modified polyolefin.

[0067] Preparation of zero-dimensional functionalized nano-TiO2: B1. Prepare a 50 g / L suspension of 50 g nano TiO2 with deionized water, adjust the pH to 4.0 with ω=5% acetic acid solution, then disperse at high speed with emulsifier for 20 min, and then disperse by ultrasonication for 30 min before transferring to a three-necked flask.

[0068] B2. Add 20% by mass of nano-TiO2 and silane coupling agent KH560 to the three-necked flask in B1, place it in a constant temperature water bath to maintain the reaction temperature at 80℃, react for 8 hours under stirring, then centrifuge, filter and wash, extract with anhydrous ethanol for 2 hours, and vacuum dry and pulverize at 60℃ to obtain functionalized nano-TiO2.

[0069] The preparation process of two-dimensional graphene oxide is as follows: C1. Under an ice-water bath, add 50 parts of concentrated sulfuric acid to a three-necked flask containing 10 parts of natural graphite powder and stir until homogeneous. C2. Slowly add 8 parts of potassium permanganate to the three-necked flask of C1, stir well, and then raise the temperature to 35℃ and react for 30 minutes. C3. After adding 50 parts of deionized water to the C2 reaction system, the temperature is raised to 90℃ and the reaction continues for 30 minutes. After the reaction is completed, 5 parts of hydrogen peroxide are added, filtered and washed, and then ultrasonically treated for 30 minutes to form two-dimensional graphene oxide.

[0070] Furthermore, the C / O atomic ratio of the two-dimensional graphene oxide is 1.32, and the interlayer spacing is 0.85 nm.

[0071] A method for preparing a multi-scale modified asphalt additive includes the following steps: S1. Spray 8 parts of interface agent evenly onto 62 parts of modified polyolefin while stirring, so that the interface agent forms a uniform oil film on the surface of modified polyolefin. S2. Add 30 parts of functionalized nano-TiO2 evenly into the material in S1 and mix them evenly by high-speed stirring. S3. The material that is uniformly mixed in S2 is melted, extruded and granulated to form the main additive. The temperature of the melt extrusion section is 120~160℃.

[0072] S4. Add 0.8 parts of one-dimensional aminated carbon nanotubes and 0.2 parts of two-dimensional graphene oxide into a high-speed disperser and mix evenly to form an auxiliary additive.

[0073] The following is a method for using a multi-scale modified asphalt additive: P1. Add the additives at 1% of the asphalt mass ratio into the asphalt storage tank, and stir at 1000 rpm for 1 hour at 160~170℃ to form nano-modified asphalt.

[0074] P2. Add the main additive to the mixing tank of the asphalt mixing plant at 1.4% of the mass ratio of the aggregate, and dry mix it with the hot aggregate preheated to 180-190℃ for 15-20 seconds; so that the main additive is completely melted and spread on the surface of the hot aggregate.

[0075] P3. Inject nano-modified asphalt preheated to 160-170℃ into the mixing tank of the asphalt mixing plant at 3.9% of the aggregate mass ratio, and continue mixing for 30-40 seconds. P4. Add mineral powder into the mixing tank of the asphalt mixing plant according to the production mix ratio, and continue to stir for 30-40 seconds until there are no white particles, forming a modified asphalt mixture. P5. Place the modified asphalt mixture prepared in P4 into a material truck for transportation, paving, and compaction.

[0076] Example 3 Performance Test: Table 3. Detection results of multi-scale modified asphalt additives in Example 3 Comparative Example 1 (Main and auxiliary additives are directly added simultaneously) The multi-scale modified asphalt additives provided in this comparative example include, by weight fraction, 76 parts of modified polyolefin, 20 parts of zero-dimensional functionalized nano-TiO2, and 4 parts of interface agent as the main additives; and by weight fraction, the auxiliary additives include the following components: 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of two-dimensional graphene oxide.

[0077] This comparative example uses the traditional direct injection method, where the main and auxiliary additives are directly injected during the asphalt mixture mixing process. The remaining preparation process of the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0078] The method of using the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0079] Performance test of Comparative Example 1: Table 4. Test results of multi-scale modified asphalt additives in Comparative Example 1 Compared to Example 1, the dynamic stability of the modified asphalt mixture decreased from 12825 cycles / mm to 9256 cycles / mm, the low-temperature flexural failure strain decreased from 2718 to 1752, and the four-point flexural fatigue life decreased from >1 million cycles to 946,000 cycles. This indicates that when auxiliary additives and main additives are directly added simultaneously, small-particle-size auxiliary additives are prone to forming uneven agglomerates during the mixing process with aggregates. Due to their bonding with modified polyolefins, the distribution of polyolefins in the asphalt is uneven, thus failing to construct a uniform and stable micro-nano structure. Consequently, its dynamic stability, low-temperature flexural failure strain, and four-point flexural fatigue life are all significantly reduced compared to Example 1.

[0080] Comparative Example 2 (Unmodified Polyolefin): The multi-scale modified asphalt additives provided in this comparative example include, by weight fraction, 76 parts of polyolefin, 20 parts of zero-dimensional functionalized nano-TiO2, and 4 parts of interface agent as the main additives; and by weight fraction, the auxiliary additives include the following components: 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of two-dimensional graphene oxide.

[0081] This comparative example uses ungrafted polyolefin instead of modified polyolefin, and the rest of the preparation process of the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0082] The method of using the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0083] Performance test of Comparative Example 2: Table 5. Test results of multi-scale modified asphalt additives in Comparative Example 2 Compared to Example 1, in Comparative Example 2, the spherulite morphology of the multi-scale modified asphalt main additive changed from a small-sized uniform distribution to a larger-sized non-uniform distribution. The segregation of the main and auxiliary additive composite modified asphalt increased significantly from 1.9℃ to 10.3℃. The low-temperature flexural failure strain of the modified asphalt mixture decreased from 2718 to 2014, and the four-point flexural fatigue life decreased from >1 million cycles to 923,000 cycles. This indicates that the unmodified polyolefin has poor compatibility with functionalized nano-TiO2 and asphalt, resulting in slight agglomeration of functionalized nano-TiO2 in the polyolefin and insignificant grain refinement effect. This leads to relatively uneven distribution of the asphalt, resulting in uneven crystallization at medium and low temperatures. Consequently, its low-temperature flexural failure strain and four-point flexural fatigue life are significantly reduced compared to Example 1.

[0084] Comparative Example 3 (Unmodified Nano TiO2): The multi-scale modified asphalt additives provided in this comparative example include, by weight fraction, 76 parts of modified polyolefin, 20 parts of zero-dimensional nano-TiO2, and 4 parts of interface agent as the main additives; and by weight fraction, the auxiliary additives include the following components: 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of two-dimensional graphene oxide.

[0085] In this comparative example, unmodified zero-dimensional nano-TiO2 was used instead of zero-dimensional functionalized nano-TiO2. The rest of the preparation process of the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0086] The method of using the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0087] Performance test of Comparative Example 3: Table 6. Test results of multi-scale modified asphalt additives in Comparative Example 3 Compared with Example 1, in Comparative Example 3, the spherulite morphology of the multi-scale modified asphalt main additive changed from a small-sized uniform distribution to a larger-sized non-uniform distribution; the segregation of the main and auxiliary additive composite modified asphalt increased significantly from 1.9℃ to 2.8℃; the low-temperature bending failure strain of the modified asphalt mixture decreased from 2718 to 1902, and the four-point bending fatigue life decreased from >1 million cycles to 954,000 cycles. This indicates that nano-TiO2 has poor compatibility in modified polyolefins and is not uniformly dispersed in polyolefins. It does not have a significant effect on refining and improving the crystal structure of polyolefins, resulting in the modified polyolefins being distributed in a large-particle non-uniform distribution in the asphalt. The nano-TiO2 does not play an effective anchoring role in the assembly and arrangement of auxiliary additives on polyolefin particles, forming an unstable and non-uniform micro-nano structure, which easily causes stress concentration, resulting in a significant reduction in its low-temperature bending failure strain and four-point bending fatigue life compared with Example 1.

[0088] Comparative Example 4 (without added interface agent): The multi-scale modified asphalt additives provided in this comparative example include, by weight fraction, 80 parts of modified polyolefin and 20 parts of zero-dimensional functionalized nano-TiO2 as the main additives; and by weight fraction, the auxiliary additives include the following components: 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of two-dimensional graphene oxide.

[0089] This comparative example does not add an interface agent, and the proportion of the interface agent is replaced with modified polyolefin. The rest of the preparation process of the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0090] The method of using the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0091] Performance test of Comparative Example 4: Table 7. Test results of multi-scale modified asphalt additives in Comparative Example 4 Compared to Example 1, in Comparative Example 4, the spherulite morphology of the multi-scale modified asphalt main additive changed from a small-sized uniform distribution to a large-sized non-uniform distribution; the segregation of the main and auxiliary additive composite modified asphalt increased significantly from 1.9℃ to 3.6℃; the low-temperature bending failure strain of the modified asphalt mixture decreased from 2718 to 1823, and the four-point bending fatigue life decreased from >1 million cycles to 916,000 cycles. This indicates that without the addition of an interface agent, the modified polyolefin and zero-dimensional functionalized nano-TiO2 cannot be uniformly mixed during the molding process due to their size differences. This results in the formation of agglomerated particles of zero-dimensional functionalized nano-TiO2 in the modified polyolefin, which does not refine the spherulite structure of the polyolefin. Furthermore, due to the self-assembly of the agglomerated nano-TiO2 and the nano-modifiers in the auxiliary additives by van der Waals forces, they do not form a uniform micro-nano structure system that effectively transfers stress with the modified polyolefin, resulting in a significant reduction in both low-temperature bending failure strain and four-point bending fatigue life compared to Example 1.

[0092] Comparative Example 5 (Unmodified carbon nanotubes) The multi-scale modified asphalt additives provided in this comparative example include, by weight fraction, 76 parts of modified polyolefin, 20 parts of zero-dimensional functionalized nano-TiO2, and 4 parts of interface agent as the main additives; and by weight fraction, the auxiliary additives include the following components: 0.4 parts of carbon nanotubes and 0.6 parts of two-dimensional graphene oxide.

[0093] In this comparative example, unmodified carbon nanotubes were used instead of one-dimensional aminated carbon nanotubes. The rest of the preparation process of the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0094] The method of using the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0095] Performance test of Comparative Example 5: Table 8. Test results of multi-scale modified asphalt additives in Comparative Example 5 Compared to Example 1, in Comparative Example 5, the distribution of nanomodifiers in the nano-modified asphalt prepared from multi-scale modified asphalt additives changed from uniform distribution to the presence of a large number of agglomerated particles; the segregation of the main and auxiliary additive composite modified asphalt increased significantly from 1.9℃ to 2.7℃; the low-temperature bending failure strain of the modified asphalt mixture decreased from 2718 to 2237, and the four-point bending fatigue life decreased from >1 million cycles to 973,000 cycles. This indicates that unmodified carbon nanotubes themselves have large van der Waals forces, leading to self-assembly and agglomeration, failing to form an effective three-dimensional spatial structure with two-dimensional graphene oxide, resulting in uneven distribution in the nano-modified asphalt. In the micro-nano structure system composed of the main additives, they cannot play their bridging and riveting role, failing to form an interconnected micro-nano structure system, leading to a significant reduction in both low-temperature bending failure strain and four-point bending fatigue life compared to Example 1.

[0096] Comparative Example 6 (Unmodified Graphene) The multi-scale modified asphalt additives provided in this comparative example include, by weight fraction, 76 parts of modified polyolefin, 20 parts of zero-dimensional functionalized nano-TiO2, and 4 parts of interface agent as the main additives; and by weight fraction, the auxiliary additives include the following components: 0.4 parts of one-dimensional aminated carbon nanotubes and 0.6 parts of graphene.

[0097] In this comparative example, unmodified graphene was used instead of two-dimensional graphene oxide. The rest of the preparation process of the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0098] The method of using the multi-scale modified asphalt additive provided in this comparative example is the same as in Example 1.

[0099] Performance test of Comparative Example 6: Table 9. Test results of multi-scale modified asphalt additives in Comparative Example 6 Compared to Example 1, in Comparative Example 5, the distribution of nano-modifiers in the nano-modified asphalt prepared from multi-scale modified asphalt additives changed from uniform distribution to the presence of a large number of agglomerated particles; the segregation of the composite modified asphalt with main and auxiliary additives increased significantly from 1.9℃ to 2.9℃; the low-temperature flexural failure strain of the modified asphalt mixture decreased from 2718 to 2115, and the four-point flexural fatigue life decreased from >1 million cycles to 968,000 cycles. This indicates that the large van der Waals forces between the unmodified graphene layers prevent the asphalt from swelling the graphene, thus preventing the one-dimensional aminated carbon nanotubes from distributing between the graphene layers to create interlayer bridging and rivet-like effects, failing to form a three-dimensional spatial structure. Furthermore, due to the small interlayer spacing of graphene, the interlayer adsorption effect on asphalt is weak, easily forming agglomerated particles in the nano-modified asphalt, resulting in uneven distribution. This prevents the formation of an interconnected reinforcing system in the micro-nano structure system composed of the main additives, leading to a significant reduction in both low-temperature flexural failure strain and four-point flexural fatigue life compared to Example 1.

[0100] Those skilled in the art should understand that this invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A multi-scale modified asphalt additive, characterized in that, It consists of main additives and auxiliary additives, calculated by weight. The main additive comprises the following components: 60-80 parts of modified polyolefin, 20-30 parts of zero-dimensional functionalized nano-TiO2, and 4-8 parts of interface agent; The auxiliary additives include the following components: 0.4-0.8 parts of one-dimensional aminated carbon nanotubes and 0.2-0.6 parts of two-dimensional graphene oxide; The main additives are added directly in proportion during the mixing of asphalt mixtures, while the auxiliary additives are added to the base asphalt in advance and stirred to form nano-modified asphalt. The modified polyolefin is obtained by melt extrusion grafting modification of polyolefin with maleic anhydride as the main graft monomer, styrene as the co-graft monomer, and initiator. The molecular weight of the polyolefin is 15,000~25,000, and the melt index at 190℃ and 2.16kg load is 40~50g / 10min. The initiator is a mixture of BPO and TBPB with a mass ratio of 1:

1. Zero-dimensional functionalized nano-TiO2 was prepared by solution grafting of nano-TiO2 and silane coupling agent; the nano-TiO2 had a rutile crystalline morphology, a particle size of 20-25 nm, and a specific surface area of ​​50-60 m². 2 / g; The interface agent is one or more of naphthenic oil and white oil, and the kinematic viscosity of the interface agent at 40°C is 10~20 mm. 2 / s; The specific surface area of ​​one-dimensional aminated carbon nanotubes is 250~300 m². 2 / g, with an average tube diameter of 10~15nm, an average length of 3~5μm, and an amino content of 0.45wt%; Two-dimensional graphene oxide is obtained by oxidizing natural graphite powder sequentially with concentrated sulfuric acid and potassium permanganate. The C / O atomic ratio of two-dimensional graphene oxide is 1.3~1.5, and the interlayer spacing is 0.8~0.9 nm.

2. The multi-scale modified asphalt additive according to claim 1, characterized in that, The mass ratio of the polyolefin, the maleic anhydride, the styrene, and the initiator is 100:2~3:0.4~0.6:0.1~0.

3.

3. The multi-scale modified asphalt additive according to claim 1, characterized in that, The amount of the silane coupling agent is 10% to 20% of the mass fraction of nano-TiO2.

4. The multi-scale modified asphalt additive according to claim 1, characterized in that, The mass ratio of the natural graphite powder, the concentrated sulfuric acid, and the potassium permanganate is 10:40~50:4~8.

5. A multi-scale modified asphalt additive according to claim 1 or 2, characterized in that, The preparation method of the modified polyolefin includes the following steps: A1. Dissolve maleic anhydride, styrene, and initiator in acetone; A2. Add the polyolefin to the solvent in A1 and stir until homogeneous; A3. The polyolefin in A2 is melt-extruded and granulated using a twin-screw extruder to form a modified polyolefin.

6. A multi-scale modified asphalt additive according to claim 1 or 4, characterized in that, The preparation method of the two-dimensional graphene oxide includes the following steps: C1. Add concentrated sulfuric acid to natural graphite powder and stir until well mixed; C2. Add potassium permanganate and react at 35°C; C3. After adding deionized water, react at 90℃ to obtain two-dimensional graphene oxide.

7. A method for preparing a multi-scale modified asphalt additive according to any one of claims 1 to 4, characterized in that, The following steps are included: S1. Premix the modified polyolefin and the interface agent in a certain proportion; S2. Mix the zero-dimensional functionalized nano-TiO2 and the materials in S1 evenly; S3. The material from S2 is fed into a twin-screw extruder and melted, extruded, and granulated to form the main additive; S4. Mix one-dimensional aminated carbon nanotubes and two-dimensional graphene oxide evenly to form an auxiliary additive.

8. The method of using a multi-scale modified asphalt additive according to any one of claims 1 to 4, characterized in that, The following steps are included: P1. Add the auxiliary additives at 1% of the asphalt mass ratio into the asphalt storage tank and stir until evenly mixed. P2. Add the main additive to the mixing tank and mix it with the ore at a ratio of 0.8% to 1.4% by mass of the ore. P3. Add asphalt binder at 3.9% to 4.5% of the aggregate mass ratio and mix thoroughly. P4. Add mineral powder according to the production mix ratio and mix evenly to form modified asphalt mixture; P5. Place the well-mixed modified asphalt mixture from P4 into a material truck for transportation, paving, and compaction.

Citation Information

Patent Citations

  • Wearable electrophysiological monitoring systems

    WO2024168218A1

  • Low-carbon, carbon-neutral, and carbon-negative asphalt composites using functionalized biochar

    WO2025222191A2